Exploring stress in the nursing profession: A Qualitative study, using semi-structured interviews - Simon, Danielle Tyla (The IIE, 2020)
The present research study is created to explore how nurses perceive the stress associated with their nursing profession. This is due to the fact that stress is an ongoing phenomenon being experienced, it is thus considered necessary to find out factors create this perception of a stressful profession (Koinis et al., 2015). Four nurses both female and male participants were contacted using non-random, convenience purposive sampling. The study is in qualitative nature and made use of semi-structured interviews as a data collection method that allowed participants' perceptions and experiences to be captured, in relation to stress within the nursing profession. In addition, the study used thematic data analysis methods. From this, major findings revealed that for participants, factors that they perceive as stressful in the nursing profession include; long hours, demanding environment and being understaffed. They also suggested that it is vital to find the sufficient ways of coping because there are currently no readily available coping strategies. Findings/contributions and factors indicated that stress in the nursing profession is an ever increasing phenomenon that does not have the sufficient coping mechanisms to reduce stress in the nursing profession.
Keywords: Nursing profession; Stress; Effects of stress; Perceptions; Coping strategies